Dust in and near the orion nebula - C. R. O`Dell (Revista Mexicana de Astronomía y Astrofísica, 2002)
Although the blister model for the Orion Nebula is widely accepted, an alternative model, where the opticalappearance of the nebula is primarily determined by self-extinction, continues to be considered by some andhas never specically been disproven. I summarize the characteristics of the two models and show that theevidence falls overwhelmingly against the self-extinction model and in favor of the blister model.